Meningkatkan Literasi melalui Metode Batu-Basah pada Siswa di Sekolah Dasar Kota Samarinda - Mulyati, Sri (BEduManagers Journal : Borneo Educational Management and Research Journal, 2023)
The purpose of this study was to improve the reading culture of elementary school children using the Batu Wet method, where the activity was carried out for three days. The problem that exists today is the lack of students reading, especially in non-educational books, which researchers teach using the wet stone method and are carried out for three days. This research method is a descriptive qualitative method where the data source comes from research results and secondary data comes from research results published in the form of publications. The data analysis technique used is data reduction to conclusions (observation results, student activity forms and student presentations). The results of this study were that on the first day of observation it was found that several students were still not very enthusiastic about participating in activities. On the second and third day of observation it was seen that students' interest in reading increased as reflected in the enthusiasm of students to take part in this reading and writing activity. Based on the results of the study it can be concluded that the Batu Wet method can be used to improve the reading culture and courage of class III students at SDN 007 Samarinda Ulu